2021
DOI: 10.1002/rmv.2247
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between blood groups and risk of infection with SARS‐CoV‐2 or development of severe outcomes: A review

Abstract: Summary The outbreak of coronavirus disease 2019 (COVID‐19), caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) is considered a global catastrophe that has overwhelmed health care systems. Since initiation of the pandemic, identification of characteristics that might influence risk of infection and poor disease outcomes have been of paramount interest. Blood group phenotypes are genetically inherited characteristics whose association with certain infectious diseases have long bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 97 publications
1
16
0
1
Order By: Relevance
“…There are several studies indicating that the AB0 blood group might be an important factor regarding an infection with SARS-CoV-2 [ 33 , 34 , 35 ]. Concerning the infection risk, contradictory results are available: While some studies show a significantly lower infection risk for blood group 0 [ 36 , 37 , 38 , 39 , 40 , 41 ], others show no specific infection risk for any AB0 blood group [ 21 , 42 , 43 ]. Different cohort groups studied might explain discrepant results: While those studies documenting a lower infection risk for blood group 0 mainly focus on patients with severe disease course, studies indicating no difference focus on cases of rather mild disease course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies indicating that the AB0 blood group might be an important factor regarding an infection with SARS-CoV-2 [ 33 , 34 , 35 ]. Concerning the infection risk, contradictory results are available: While some studies show a significantly lower infection risk for blood group 0 [ 36 , 37 , 38 , 39 , 40 , 41 ], others show no specific infection risk for any AB0 blood group [ 21 , 42 , 43 ]. Different cohort groups studied might explain discrepant results: While those studies documenting a lower infection risk for blood group 0 mainly focus on patients with severe disease course, studies indicating no difference focus on cases of rather mild disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Different cohort groups studied might explain discrepant results: While those studies documenting a lower infection risk for blood group 0 mainly focus on patients with severe disease course, studies indicating no difference focus on cases of rather mild disease course. However, there is growing evidence that blood group 0 has a lower risk for severe disease course [ 39 , 44 ]. Furthermore, AB individuals were demonstrated to have a higher risk for a SARS-CoV-2 infection [ 35 , 45 ], severe disease course including the necessity of ventilation [ 33 , 34 ] and increased mortality [ 33 ] compared to other AB0 blood groups.…”
Section: Discussionmentioning
confidence: 99%
“…from India, have reported similar observations on blood group association with neutralizing antibodies and have found neutralising antibodies in significantly higher percentage of people with blood group AB (0.36), followed by B (0.31), A (0.22) and lowest in people with blood group O (0.11). Difference between blood group AB versus O was highly statistically significant p<0.001) [33]. Some studies have reported that non-O blood group individuals are at higher risk of developing COVID-19 in comparison to O blood group and they have postulated that this is either due to natural antibodies against blood group antigens acting as a part of innate immune response to neutralize viral particles or alternatively, blood group antigens maybe acting as additional receptors for the virus and individuals who are capable of expressing these antigens on epithelial cells, would possibly have a high propensity to be affected by SARS-CoV-2 [34][35][36].…”
Section: Discussionmentioning
confidence: 85%
“…32 -7 of 11 32 with HIV 39 ; TMPRSS2, 40 TLR-3 genes with influenza 41,42 ; and blood group with dengue. 43 Throughout last year, 20 genetic association studies were conducted. The most evaluated single locus was the ABO, and the most sampled region was the HLA with three 23,32,33 and five 18,19,22,28,30 candidate gene studies, respectively.…”
Section: Resultsmentioning
confidence: 99%